TECHNOLOGY IMPLEMENTATION STRATEGY AT AMIL ZAKAT INSTITUTIONS - Suci Ramadhani; Shella Dwi Indina Syahputri; Riyan Pradesyah (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the application of information technology through ZISWAF (Zakat, Infaq, Alms, and Waqf) at LAZ Alwashliyah. This research focuses on LAZ Alwashliyah in collecting and distributing ZISWAF funds and how to manage ZISWAF through information technology. This research uses a qualitative method based on a descriptive study. Data collection techniques using observation, and direct question and answer. Data analysis was carried out in stages, namely data reduction, data presentation, and drawing conclusions. Test the validity of the data using triangulation. The results of the study indicate that the implications of information technology in LAZ Alwashliyah have been carried out. This can be seen with the application of information technology in the form of the LAZ Alwashliyah Website in the collection and distribution of infaq, alms, and waqf funds to date. With the ZIS fundraising process carried out at LAZ Alwashliyah using two methods, the first online and the second offline. In addition to collection, the process of distributing zakat is still offline with the method of going directly to the field and seeing the economy and giving it to people who are entitled to receive it.